Assessment of Heavy Metal Pollution in Groundwater in the Hindon River Basin Using Pollution Index - Singh Bhanu Pratap; Gupta Piyush (E3S Web of Conferences)
This study presents heavy metal levels, including cadmium (Cd), copper (Cu), chromium (Cr), iron (Fe), manganese (Mn), zinc (Zn) and lead (Pb) in groundwater in the Hindon River basin, a region of high agricultural and industrial activity. These parameters were analyzed over different seasons, i.e. summer (April to June), Monsoon (July to September) and winter (October to December) during 2023. The results of this analysis are crucial for understanding the current state of groundwater quality in the Hindon River basin. Water samples were collected from the different sampling stations, strategically distributed across the Hindon River basin, to ensure a comprehensive understanding of the water quality in the region. Sampling was conducted thrice at each sampling point across different seasons. The stations encompass Sampling Site C (comprising sampling points C1 to C10). The Heavy Metal Pollution Index (HPI) was employed to evaluate water quality at specified sites. Mean HPI values were 132.05 in summer, 97.48 in the monsoon season, and 114.24 in winter. The average HPI suggests extreme contamination levels throughout the study area in all seasons. The correlation coefficient provides valuable insights into the complex relationships between different heavy metals in groundwater, supporting the assessment and understanding of sources of heavy metal pollution. The research findings underscore the situation's urgency, indicating that the water was unsafe for consumption without appropriate treatment. This highlights the critical need for ongoing groundwater monitoring to address heavy metal contamination, urging stakeholders to take immediate action.